Isolation of Genomic DNA from Blood Using a Novel Filter-Based DNA Purification Technology. (July 2001) - Baker, M.P.; Mitchell, A.; Bridge, C.; Martin, S.; Holder, F.; Pathirana, N.D.; Jarvis, A.; Butt, N.
A novel DNA purification technology is described that enables the purification of pure dsDNA from blood. When compared to existing DNA purification methods, the Whatman BioScience Purification System (WBPS) offers a fast and convenient way to recover high yields of DNA. WBPS is based on a unique filter system that entraps DNA within a matrix. This allows the process to be performed in a single unidirectional reaction vessel, reducing user interaction and multiple centrifugation steps.